Puisi Angka Jawa sebagai Indigenous Knowledge dalam Perspektif Etnomatematika Sastra - Suwardi Endraswara (Aksara, 2023)
This article aims to interpret Javanese number poetry texts. These number poems, apart from being symbols of intelligence, are also symbols of Javanese indigenous knowledge. The study uses qualitative interpretive ethnographic methods. Meaning is also studied using a literary ethnomathematics perspective. The Javanese number poetry data appears in four forms, namely: (1) macapat, (2) dolanan songs, (3) karawitan literature, and (4) geguritan. The Javanese numeric poetry data is read heuristically, then interpreted hermeneutically. This study emphasizes transdisciplinary studies. The results of the study show that in Javanese life, there are various number poems. After understanding the Javanese number poetry, it uses four perspectives of meaning, namely: (1) Ethnomathematics of literary analogies, (2) Ethnomathematics of literary anthropology, (3) Ethnomathematics of literary pedagogy, and (4) Ethnomathematics of Literary Memory. Through these four perspectives, Javanese number poetry is found as an illustration of the philosophy of indigenous knowledge. The text of the poem contains local analogies about numbers. The mathematical poem with the dhandhanggula meter actually depicts numbers starting from 1, 2, 3, 4, 5, 6, 7, 8, 9, and 0. The Javanese number poem is an invitation to encourage students to behave, among other things: ( 1) working hard, (2) working together, (3) helping each other, (4) getting along harmoniously, and (5) mutual cooperation. This study of Javanese number poetry is useful for providing an overview of the intelligence of the Javanese people. In the future, it is necessary to study further the Javanese number poetry that appears in various Javanese literary genres.AbstrakArtikel ini bertujuan untuk memaknai teks-teks puisi angka Jawa. Puisi-puisi angka itu, selain sebagai simbol kecerdasan juga sekaligus lambang indigenous knowledge orang Jawa. Kajian menggunakan metode kualitatif interpretatif etnografi. Makna juga dikaji menggunakan perspektif etnomatematika sastra. Data puisi angka Jawa tersebut muncul dalam empat bentuk, yaitu (1) macapat, (2) lagu dolanan, (3) sastra karawitan, dan (4) geguritan. Data-data puisi angka Jawa itu dibaca secara heuristik kemudian ditafsirkan secara hermeneutik. Kajian ini menekankan kajian transdisipliner. Hasil kajian menunjukkan bahwa dalam kehidupan orang Jawa, terdapat beragam puisi angka. Puisi angka Jawa tersebut setelah dipahami menggunakan empat perspektif pemaknaan, yaitu (1) Etnomatematika Analogi Sastra, (2) Etnomatematika Antropologi Sastra, (3) Etnomatematika Pedagogi Sastra, dan (4) Etnomatematika Memori Sastra. Melalui empat perspektif tersebut ditemukan puisi angka Jawa sebagai gambaran falsafah indigenous knowledge. Teks puisi tersebut memuat analogi lokal tentang angka. Puisi matematika bermetrum dhandhanggula itu, sesungguhnya melukiskan angka-angka mulai dari 1, 2, 3, 4, 5, 6, 7, 8, 9, dan 0. Puisi angka Jawa merupakan  ajakan untuk mendorong peserta didik memiliki perilaku (1) bekerja keras,  (2) bekerja sama, (3) saling membantu, (4) guyup rukun, dan (5) gotong royong. Kajian puisi angka Jawa ini berguna untuk memberikan gambaran kecerdasan orang Jawa. Ke depannya perlu dikaji lebih lanjut puisi angka Jawa yang muncul dalam berbagai genre sastra Jawa.